Volumetric and calorimetric properties of aqueous ionene solutions - Lukšič, Miha (Journal of molecular liquids, 2017)
The volumetric (partial and apparent molar volumes) and calorimetric properties (apparent heat capacities) of aqueous cationic polyelectrolyte solutions - ionenes - were studied using the oscillating tube densitometer and differential scanning calorimeter. The polyion's charge density and the counterion properties were considered as variables. The special attention was put to evaluate the contribution of electrostatic and hydrophobic effects to the properties studied. The contribution of the CH2 group of the polyion's backbone to molar volumes and heat capacities was estimated. Synergistic effect between polyion and counterions was found